Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Sabun Antibakteri Ramah Lingkungan Berbahan Minyak Jelantah - Fadilah Qonitah (Universitas Sahid Surakarta, 2026)
Used cooking oil is a form of household waste that has the potential to pollute the environment and pose a health risk if reused repeatedly or disposed of improperly. This community service initiative aims to improve the community’s knowledge and skills in processing used cooking oil into environmentally friendly antibacterial soap. The activity was carried out in Karangasem Village, Laweyan Sub-district, Surakarta, involving local women through educational sessions, soap-making training, mentoring, and evaluation (pre-tests and post-tests). The results of the activity showed an increase in participants’ knowledge, as evidenced by a 27.9 per cent rise in the average score between the pre test and post test. Furthermore, participants actively took part in the community service activity. This initiative also raised public awareness of the importance of sustainable used cooking oil management and encouraged its utilisation to create environmentally friendly products with economic value.